Digital cutting board / Muhammad Shazwan Abd. Musalleb - Abd. Musalleb, Muhammad Shazwan; Mohd Lotpi, Nurul Shafikah; Aman, Nor Amalina; Norijan, Nor Zaheeda (2017)
After years and years using the traditional way of cooking, the team had built a product that we believe can make changes when cooking a meal. Hence, our team introduced Digital Cutting Board (DCB) to all the cooking lover. Nowadays, the interest of cooking and preparing meal has grown profoundly for both men and women. Everyone now has enjoyed cooking including the children. Besides that, cooking is essential for daily live since it is the source of energy to work, play and live. This product is suitable for those who likes to prepare their own home cooking or for housewives.